Tonal change and neutralization - Kubozono, Haruo; Giriko, Mikio (Phonology and Phonetics PP Ser., 2018)
"This is the first book on tonal change and neutralization. It covers a wide range of tone and pitch-accent languages in Asia, Africa and Europe, with a main focus on Japanese and Chinese dialects many of which are now endangered. In addition to presenting unpublished data, the book provides novel typological analyses of tone and neutralization"--